Bridgeless single‐phase step‐down PFC converter. Issue 14 (1st November 2016) - Malekanehrad, Mahdi; Adib, Ehsan
Abstract : This study presents a bridgeless single‐phase step‐down power factor correction (PFC) converter. The proposed converter consists of a buck converter in positive half‐line cycle and a flyback converter in the negative one. The dead angle of input line current is omitted so high power factor (PF) and low total harmonic distortion (THD) are obtained. There are just two simultaneously conducting semiconductor devices in the charging path of buck and flyback inductors that reduce the conduction losses. A 80 W, 24 V experimental prototype verifies the operation of the proposed rectifier and a PF of 0.995 and THD <10% can be achieved.